Tet-on, or Tet-off, that is the question: Advanced conditional gene expression in Aspergillus - Wanka, Franziska; Cairns, Timothy; Boecker, Simon; Berens, Christian; Happel, Anna; Zheng, Xiaomei; Sun, Jibin; Krappmann, Sven; Meyer, Vera (Fungal Genetics and Biology, 2015)
In Aspergillus, controlled gene expression is often achieved using the reverse tetracycline-controlled transactivator (rtTA) dependent Tet-on system, whereby transcription is activated in a titratable manner by addition of the tetracycline derivative doxycycline. The complementary Tet-off system utilises the tetracycline-controlled transactivator (tTA) component to quantitatively reduce gene expression. In this study, we utilised a synthetic biological approach to engineer highly optimised Tet-off conditional expression systems in Aspergillus niger and Aspergillus fumigatus. Steps for delivery of these tools include utilising codon optimised cassette components, testing several promoters for improved genetic stability and validating two modified luciferase reporters for highly accurate measurements of gene expression. The Tet-off cassettes developed in this study enable facile and quantitative functional analysis, as validated by Tet-off analysis of genes involved in chitin synthesis and cell wall polarity in A. niger, and para-aminobenzoic acid synthesis in A. fumigatus. We also used a racA(G18V) dominant allele to demonstrate that Tet-off in A. niger enables gene over-expression and downregulation in a single isolate. Additionally, we used the improved luciferase reporters to show that the Tet-off cassette in A. niger enables quantification of gene oscillations. In order to demonstrate that synthetic biological approaches developed here are broadly applicable to engineering transcriptional circuits in filamentous fungi, we used our strategy for improving cassette stability by promoter replacement in the A. niger Tet-on system, which resulted in a modified Tet-on cassette with higher stability in recipient genomes.
EVALuna2:7694